Sociocultural determinants of home delivery in Ethiopia: a qualitative study - Kaba M; Bulto T; Tafesse Z; Lingerh W; Ali I (Dove Medical Press, 2016)
Mirgissa Kaba,1 Tesfaye Bulto,2 Zergu Tafesse,2 Wassie Lingerh,2 Ismael Ali2 1Department of Preventive Medicine, School of Public Health, Addis Ababa University, 2Integrated Family Health Program, John Snow, Inc., Addis Ababa, Ethiopia Background: Maternal health remains a major public health problem in Ethiopia. Despite the government’s measures to ensure institutional delivery assisted by skilled attendants, home delivery remains high, estimated at over 80% of all pregnant women.Objective: The study aims to identify determinants that sustain home delivery in Ethiopia.Methods: A total of 48 women who delivered their most recent child at home, 56 women who delivered their most recent child in a health facility, 55 husbands of women who delivered within 1 year preceding the study, and 23 opinion leaders in selected districts of Amhara, Oromia, Southern Nations, Nationalities, and Peoples’ Region, and Tigray regions were involved in the study. Key informant interview, in-depth interviews, and focus group discussions were conducted to collect data using checklists developed for this purpose. Data reduction and analysis were facilitated by Maxqda qualitative data analysis software version 11.Results: Findings show that pregnancy and delivery is a normal and natural life event. Research participants unanimously argue that such a life event should not be linked with health problems. Home is considered a natural space for delivery and most women aspire to deliver at home where rituals during labor and after delivery are considered enjoyable. Even those who delivered in health facilities appreciate events in connection to home delivery. Efforts are underway to create home-like environments in health facilities, but health facilities are not yet recognized as a natural place of delivery. The positive tendency to deliver at home is further facilitated by poor service delivery at the facility level. Perceived poor competence of providers and limited availability of supplies and equipment were found to maintain the preference to deliver at home.Conclusion: The government’s endeavor to improve maternal health has generated positive results with more women now attending antenatal care. Yet over 80% of women deliver at home and this was found to be the preferred option. Thus, the current form of intervention needs to focus on factors that determine decisions to deliver at home and also focus on investing in improving service delivery at health facilities. Keywords: maternal health service, utilization of maternal health, antenatal care, cultural determinants